2016
DOI: 10.1016/j.marenvres.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Microbial hitchhikers on marine plastic debris: Human exposure risks at bathing waters and beach environments

Abstract: 1011

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(138 citation statements)
references
References 114 publications
3
127
2
6
Order By: Relevance
“…In 2015, De Tender et al (2015 reported the detection of members of the family Vibrionaceae on marine plastics from the Belgian North Sea. Recently a review of Keswani et al (2016) highlights the lack of knowledge about the persistence of potentially pathogenic Vibrio spp. on plastic debris.…”
Section: Vibrio Hitchhikersmentioning
confidence: 99%
“…In 2015, De Tender et al (2015 reported the detection of members of the family Vibrionaceae on marine plastics from the Belgian North Sea. Recently a review of Keswani et al (2016) highlights the lack of knowledge about the persistence of potentially pathogenic Vibrio spp. on plastic debris.…”
Section: Vibrio Hitchhikersmentioning
confidence: 99%
“…1 have been investigated with reference to microplastics. However, efforts to identify factors driving the formation of these assemblages in marine habitats have recently been reviewed [12,13,20]. Microplastics are rapidly colonized by environmental microorganisms (within hours; [21]).…”
Section: Factors Contributing To Biofilm Formation and Compositionmentioning
confidence: 99%
“…In addition to contributions from organic matter input and upwelling, high concentrations of nutrients (e.g., nitrogen and phosphorus) are released by agriculture and other human activities. Many plastisphere members have been affiliated with pollutant degradation [12,13,20,21], and it is probable that several contaminants play a role in shaping biofilm formation and activities on polymers (Fig. 1).…”
Section: Factors Contributing To Biofilm Formation and Compositionmentioning
confidence: 99%
See 2 more Smart Citations